Desain Pembangkit Listrik Tenaga Piko Hidro Terapung (PLTPHT) - Suparman Suparman; Hadi Suyono; Rini Nur Hasanah (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2017)
Potential renewable energy source in Indonesia today for hydropower around 75.67 GW and newly used about 4.2 GW. Utilization of energy in the present has been directed to the use of renewable energy in nature. Based on that idea, innovation and testing are done by designing Floating hydro power plant (FHPP) FHPP is designed by utilizing irrigation water sources to meet small-scale power consumption, especially for household consumers with 450-500 watts of power. FHPP design process is done by first analyzing the related data such as planned power and other related variables. After the size and dimensions of FHPP is known the next stage is to make the model FHPP using Ansys 18.00 software, the goal to find the optimal design of FHPP which can generate electrical power between 300-450 watts. While the components of FHPP itself consists of pontoon, waterwheel, permanent magnet generator (GMP) as an electricity generator, voltage rectifier, voltage stabilizer and battery that serves to store voltage generated by GMP. After FHPP design is completed the next stage is the mechanical testing of FHPP by using an electric motor as a substitute for water flow and experimental testing conducted by utilizing irrigation water flow. From this test obtained voltage generated by gmp is direct current (DC) with a maximum power of 480 Watt, 600 gpm rpm rotation with maximum torque of gmp of 0.42 kgm. The resulting voltage is converted to alternating current (AC) by using a converter so that it can be used to meet household electrical needs.Â Â